'I like to feel needed, you know?': a qualitative examination of sense of purpose in older care home residents. (1st February 2023) - Owen, Rebecca; Berry, Katherine; Brown, Laura J. E.
Abstract: Objectives: To explore older care home residents' experiences of maintaining a sense of purpose in life: a core component of psychological wellbeing. Methods: Fifteen residents (9 female; 6 male), aged 60-95 years, from four care homes, were interviewed about their sense of purpose. Interview transcripts were analysed using inductive thematic analysis. Results: Theme 1 ('Experiencing Loss') comprises two sub-themes that describe the impact of age-related losses on residents' sense of purpose (sub-theme 1) and the different responses that participants had to these losses (sub-theme 2). Theme 2 ('The Protective Effects of Social Connections') describes how social relationships could provide a sense of purpose, as well as the difficulties participants experienced in forming these relationships. Finally, theme 3 ('The Roles of Activities') describes the types of activities that could help residents to maintain a sense of purpose. Conclusion: Care home residents experience losses and barriers that make it more difficult to maintain a sense of purpose. However, with appropriate support and opportunities, residents are able to engage in activities and relationships that provide a sense of purpose. To support residents' mental health and wellbeing, care homes should offer varied opportunities for residents to engage in purposeful activities.